Risk assessment of personal exposure to polycyclic aromatic hydrocarbons and aldehydes in three commercial cooking workplaces - Wu, Ming-Tsang; Lin, Pei-Chen; Pan, Chih-Hong; Peng, Chiung-Yu (Scientific reports, 2019)
Cooking-related emissions are associated with environmental pollution and adverse health effects. Of the various chemical species emitted during cooking, polycyclic aromatic hydrocarbons (PAHs) and aldehydes are two chemical species with carcinogenic or tumor promoting characteristics. Although PAH exposure has been studied in commercial kitchen workers, few studies have investigated simultaneous exposure to PAHs and aldehydes in these workers. The aims of this study were to compare personal concentrations of PAH and aldehyde in three commercial cooking workplaces and to estimate their corresponding cancer risks. The three cooking workplaces included western fast food restaurant kitchens, Chinese cafeteria kitchens, and street food carts. Comparisons showed that workers in western fast food restaurant kitchens and Chinese cafeteria kitchens tended to have lower personal concentrations of these pollutants compared to workers in street food carts. The geometric mean (95% CI) cancer risks in the three workplaces were, from lowest to highest, 1.36 (1.12–1.67) × 10 −5 for western fast food restaurant kitchens, 1.52 (1.01–2.28) × 10 −5 for Chinese cafeteria kitchens, and 3.14 (2.45–4.01) × 10 −5 for street food carts. The percentage contributions of aldehyde species to cancer risk were very high (74.9–99.7%). Street food cart workers had high personal exposure to aldehyde probably due to lack of effective exhaust systems. Thus, their cancer risk was significantly higher than those of workers in western fast food restaurant kitchens (p < 0.001) and Chinese cafeteria kitchens (p = 0.013).